2005
DOI: 10.1119/1.1943431
|View full text |Cite
|
Sign up to set email alerts
|

Protein gel electrophoresis in the undergraduate physics laboratory

Abstract: We describe an undergraduate laboratory experiment in protein gel electrophoresis that uses readily available apparatus and materials. The separation of a mixture of stained proteins by gel electrophoresis was videotaped. Position–time data for the proteins generated from analysis of digitized videotape images allowed for calculation of protein terminal velocities. The dependence of protein terminal velocity on molar mass was determined and found to agree with predictions made by current theory. We also introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…15.9 nm), leading to a lower deposition rate. 29 We observed that light could be well-scattered for both of the deposited MTN and P90 films, and that the films could be easily damaged by scratching because of their poor intrinsic mechanical strength. However, adhesion of the films to the plastic substrates was so strong that the films could not be peeled off even after bending the electrodes.…”
Section: Fabrication Of Mtn and P90 Films By Epd Processesmentioning
confidence: 78%
“…15.9 nm), leading to a lower deposition rate. 29 We observed that light could be well-scattered for both of the deposited MTN and P90 films, and that the films could be easily damaged by scratching because of their poor intrinsic mechanical strength. However, adhesion of the films to the plastic substrates was so strong that the films could not be peeled off even after bending the electrodes.…”
Section: Fabrication Of Mtn and P90 Films By Epd Processesmentioning
confidence: 78%
“…(1) vanishes; in this case, one can solve for the velocity as vf = qElk. Equation (2) can be rewritten as = V, l-e (3) Equation (3) is experimentally relevant since one no longer has to quantify the drag coefficient k a priori. Instead, one can experimentally measure the terminal velocity of the molecule and rescale a theoretical curve to match up with empirically derived data.…”
Section: The Equations Of Motionmentioning
confidence: 99%
“…The detection of enzyme activity on electrophoretic gels, or zymography, has become an important tool to evaluate and analyze many enzymes [18][19][20][21][22][23][24], and has received attention on educational journals as well [25][26][27][28][29][30]. The use of zymography to instruct students in the biochemistry laboratory for the study of catalysis mechanisms or to follow activity in purification steps as well as biochemical characterization has also been reported [31][32][33].…”
mentioning
confidence: 99%
“…The use of zymography to instruct students in the biochemistry laboratory for the study of catalysis mechanisms or to follow activity in purification steps as well as biochemical characterization has also been reported [31][32][33].…”
mentioning
confidence: 99%